Teaching Italian and Reconfiguring Citizenship: The Case of Language Volunteers in Migrant Education - Artero, Maurizio (PARTECIPAZIONE E CONFLITTO, 2023)
Pro-migrant volunteering is often denounced as apolitical and patronising. Voluntary initiatives for immigrants' language education, then, have been accused of facilitating the neoliberal governmentality of migration, by fashioning migrants into precarious workers. Based on 20 in-depth interviews with volunteer language teachers in Lombardy, Italy, this article complicates such understandings, by shedding light on the tensions and ambiguities characterising volunteers' activities vis-à-vis the institutional governance of migration. Indeed, whereas such initiatives take on integration tasks for the benefit of the State, and thus can be accused of allying with the State in the governmentality of migration, against a background of growing nationalism, volunteering appears to develop people's empathy and solidarity beyond national belonging, questioning the division between citizens and non-citizens. In particular, it shows that volunteering in language education has the potential to transgress consolidated lines of inclusion and exclusion, turn volunteers from 'active citizens' into 'activist citizens', and offer resources of substantive citizenship to students. Ultimately, these 'humanitarian' actions by citizens belonging to the dominant society may represent acts of citizenship complementary to the initiatives of 'denizens'.